Simulator testing of evacuated flat plate solar collectors for industrial heat and building integration. (April 2018) - Moss, R.W.; Henshall, P.; Arya, F.; Shire, G.S.F.; Eames, P.C.; Hyde, T.
Highlights: A high vacuum increases efficiency and reduces heat losses. The vacuum enclosure concept, a cover glass supported by pins, performed well. Hydro-formed stainless steel absorber successfully demonstrated. Thermal expansion stresses led to edge seal deterioration. Abstract: The concept of an evacuated flat plate collector was proposed over 40 years ago but, despite its professed advantages, very few manufacturers have developed commercial versions. This paper demonstrates the reduction in heat loss coefficient and increase in efficiency resulting from evacuating a flat plate collector: it is hoped that these results will stimulate interest in the concept. Evacuated tubes are now mass-produced in large numbers; evacuated flat plate collectors could in principle replace these tubes if the technical difficulties in creating extended metal-glass seals can be overcome. The experimental experiences described here should indicate targets for future research. Two different designs of evacuated flat plate solar thermal collector, each with a 0.5 × 0.5 m flooded panel black chrome plated absorber, were tested under a solar simulator. The cover glasses were supported by an array of 6 mm diameter pillars. Inlet and outlet temperatures were monitored via PT100 RTDs and glass temperatures were measured using thermocouples. Inlet temperature was controlled by a fluid circulator connected to a header tank with a Coriolis mass flow meter to measure fluid flow rate. Testing was conducted indoors with and without the use of a fan to cool the top cover glass. The test conditions spanned the range 200 < G < 1000 W/m 2, 0 ⩽ T M ⩽ 52 ° C . Evacuating the enclosure reduced the measured heat loss coefficient by 3.7 W/m 2 K: this was a close match to predictions and corresponds to an increase in aperture efficiency from 0.3 to 0.6 at T M / G = 0.06 m 2 K / W . The poor efficiency under non-evacuated conditions was due to the black chrome absorber coating being less selective than commercial panel coatings. The solder seals were developed from experience with vacuum glazing but the increased gap led to reliability issues. A vacuum pump maintained the enclosures under a high vacuum (<0.1 Pa) during testing. The enclosure based on a thin rear metal tray proved to be more effectively sealed than the more rigid enclosure with glass on both sides: the latter developed leaks as the front to rear temperature difference increased. The biggest challenge in the manufacture of evacuated flat plate collectors is to ensure a long-term hermetic seal such that no pumping is required.